1970
DOI: 10.3329/bjas.v38i1-2.9906
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characteristics Of Indigenous Sheep Of Bangladesh

Abstract: This experiment was undertaken to know the phenotypic characteristics of native sheep. The study was conducted to investigate morphometric characters of sheep in three different field sites (Naogaon, Noakhali and Tangail) and Bangladesh Livestock Research Institute (BLRI) nucleus flock through close observation, measuring and record keeping. Characteristics of body weight, body length, heart girth, wither height, fore leg length, hind leg length, head length, ear length, ear width, horn length etc were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 0 publications
7
23
0
Order By: Relevance
“…Bengal breed are low to moderately prolific ( Figure 9) and the questionnaire results indicated that nearly 40 percent of the ewes had history of twinning, however the survivability of the lambs was also low which can be attributed to poor nutrition of the ewe and also due to prevailing diseases. The rams mature earlier than the ewes which in accordance with the reports of Taylor (1968).The age at sexual maturity (days) and lambing interval for the ewes are higher than those reported by Hassan and Talukder (2011) but lower than those reported by Pervage et al (2009) The variation may be attributed to management and the type of nutrition available to the ewes, reproductive parameters are influenced of both intrinsic and extrinsic factors while the former relates to the genotype the latter is influenced by the non-genetic (environmental factors), Bronson (1989), Rosa and Bryant (2003) and Ungerfeld and Bielli (2012). The reproductive parameters are also influenced by temperature, nutrition, social influences, lambing date and lactation period, Forcada and Abecia (2006) and Scaramuzzi and Martin (2008).…”
Section: Reproductive Parameters Of Bengal Sheepsupporting
confidence: 92%
See 3 more Smart Citations
“…Bengal breed are low to moderately prolific ( Figure 9) and the questionnaire results indicated that nearly 40 percent of the ewes had history of twinning, however the survivability of the lambs was also low which can be attributed to poor nutrition of the ewe and also due to prevailing diseases. The rams mature earlier than the ewes which in accordance with the reports of Taylor (1968).The age at sexual maturity (days) and lambing interval for the ewes are higher than those reported by Hassan and Talukder (2011) but lower than those reported by Pervage et al (2009) The variation may be attributed to management and the type of nutrition available to the ewes, reproductive parameters are influenced of both intrinsic and extrinsic factors while the former relates to the genotype the latter is influenced by the non-genetic (environmental factors), Bronson (1989), Rosa and Bryant (2003) and Ungerfeld and Bielli (2012). The reproductive parameters are also influenced by temperature, nutrition, social influences, lambing date and lactation period, Forcada and Abecia (2006) and Scaramuzzi and Martin (2008).…”
Section: Reproductive Parameters Of Bengal Sheepsupporting
confidence: 92%
“…The BW of the rams did not vary (P < 0.05) across the different locations (within a particular age category). The BW of the rams are in close accordance with those reported by Pervage et al (2009) for Barind sheep of Bangladesh but lower than those reported by Hassan and Talukder (2011).…”
Section: Traits Measurementssupporting
confidence: 91%
See 2 more Smart Citations
“…Sheep are reared for meat and wool production in Bangladesh (Hassan and Talukder, 2011). Indigenous sheep of Bangladesh can weigh up to 41 kilograms (Hassan and Talukder, 2011) with an annual wool production between 267 and 531g per animal per cutting (Pervage et al, 2009). Footrot may cause up to 8% lower wool production (Marshall et al, 1991), 0.5 micron drop in fibre diameter and up to 10% lower staple strength (Ware, 2005).…”
Section: Introductionmentioning
confidence: 99%